Editorial Remark Vol 6, No 1 (2023): Assessing National and International Perspectives on Justice and Legal Protection - Sitamala, Afandi (Nurani Hukum, 2023)
Journal Nurani Hukum: Journal of Legal Studies, also known as Nurani Hukum, is a peer-reviewed journal focused on legal studies. The journal aims to publish high-quality research across various areas of legal scholarship, including but not limited to law and history, legal philosophy, sociology of law, socio-legal studies, international law, environmental law, criminal law, private law, Islamic law, agrarian law, administrative law, criminal procedural law, commercial law, constitutional law, human rights law, civil procedural law, and adat law. Published by the Faculty of Law, Universitas Sultan Ageng Tirtayasa in collaboration with the Asosiasi Pengelola Jurnal Hukum Indonesia (APJHI), the journal is released biannually in June and December. Each issue is made available on the website and further distributed in hardcopy format.The current edition, Volume VI Issue 1, June 2023, covers a wide range of legal and scientific fields, including civil, criminal, constitutional, and international law. The publication of this journal is a result of the collective efforts of many individuals. We extend our gratitude to all the peer reviewers and members of the editorial board who have dedicated their time and energy to ensure the successful publication of the Journal Nurani Hukum: Journal of Legal Studies. We hope that the articles presented in this journal will serve as a valuable and enlightening resource for all readers